(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aims to measure the effectiveness of a proposed model for practical education in acquiring teaching skills at the third Year Class Teachers. The research sample consisted of two groups: The number of experimental group (120) students of the third Year Class Teachers in fourth faculty of education, the number of control group(120) students of the third Year Class Teachers in faculty of education in Damascus city. A list of teaching skills, an observation schedule and a proposed model for practical education were designed, the experimental approach was used to achieve the research objectives The search results proved what follows: the effectiveness of a proposed model for practical education in acquiring teaching skills at third Year Class Teachers 69% of the students in the experimental group achieved a level of proficiency (60-69%), While no student in the control group could reach this level of proficiency, In addition, 18% of the students in the experimental group achieved a level of proficiency (70-79%) of teaching skills. There is a statistically significant difference between the average scores of males and females of the experimental group in both my skill (planning, closing the lesson) and in the total number of teaching skills, While differences were found in each other skills and for females.